Mortality Risk Factors in Acute Upper Gastrointestinal Bleeding - Marthino Robinson; Ari Fahrial Syam; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2012)
Background: Upper gastrointestinal bleeding (UGIB) is one of the emergency cases in gastroenterology. The mortality rate does not change in the last 4 decades, however, there is no precise data in Cipto Mangunkusumo Hospital. Identified risk factors are expected to increase early awareness and optimal planning in management of patients. This study was aimed to know the mortality risk factors in acute UGIB in Cipto Mangunkusumo Hospital. Method: Case control study was performed between August and December 2011 by collecting and studying medical records of acute UGIB patients who were admitted and hospitalized between January 2003 and June 2011 in Cipto Mangunkusumo Hospital. Cases were acute UGIB patients who passed away during hospitalization in that period of time. Controls were patients who did not pass away and hospitalize in same period (date/month/year index). Samples were taken randomly with the proportion of case and control 1 : 2. Bivariate analysis was perfomed by chi-square test and continued with multivariate analysis. Results: Study subjects consisted of 87 cases and 174 controls. Significant variables as risk factors were multiple co-morbidities (OR = 2.66; 95% CI = 1.21-5.85), recurrent bleeding (OR = 9.07; 95% CI = 3.87-21.26), decreased consciousness (OR = 7.60; 95% CI = 1.94-29.88), endoscopy not performed (OR = 11.95; 95% CI = 4.75-30.11), and sepsis (OR = 4.83; 95% CI = 2.03-11.48). Conclusion: Multiple co-morbidities, sepsis, decreased consciousness on hospital admission, and recurrent bleeding are mortality risk factors in acute UGIB. Mortality risk increases in patients, to whom endoscopy was not performed. Keywords: UGI bleeding, risk factors, mortality